Simulation data for heterostructured scintillator development - Bizarri, Gregory; Rogers, Edith; Krause, Philip George; Pei, Qibing; Auffray, Etiennette; Danang Birowosuto, Muhammad; Vasil’ev, Andrey (Cranfield University, 2023)
Simulation datasets underlying the study 'Design rules for time of flight Positron Emission Tomography (ToF-PET) heterostructure radiation detectors'
Keywords: 'scintillator'; 'radiation detector'; 'heterostructured scintillator'; 'time of flight positron emission tomography'; 'ultra fast timing'